DP-internal Structure and Agreement in Nafara - Baron, Bertille (My University, 2019)
Senufo Nafara DPs show the particularly rare unmarked word order [N AP Def Dem Numeral]. In this cartographic account, the proposed derivation uses spec-to-spec movement operations to generate this word order (Cinque 2005). This analysis relies on two main claims: there is a domain ƩP under Num (Aboh 2004) in which two distinct categories of adjectives (high and low following Cinque 1994) merge to modify the noun. It is this same ƩP domain that undergoes spec-to-spec movement, motivated for agreement purposes. Oppositely, all elements structurally above ƩP remain in situ.
Keywords: Nafara; structure and agreement; Côte d’Ivoire.